2022
DOI: 10.1111/phen.12402
|View full text |Cite
|
Sign up to set email alerts
|

The peritrophic matrix delays Nosema ceranae infection in the honey bee Apis mellifera midgut

Abstract: The midgut of bees plays a significant role in digestion and absorption and is a gateway for pathogens. As a protection for the organism, the midgut lumen is lined by a peritrophic matrix rich in chitin fibrils, associated with proteins that form multiple resistant layers with gelatinous consistency, with several functions, including the mechanical barrier against infection by pathogens. The obligate intracellular microsporid Nosema ceranae is an important pathogen that decreases honey production, increases pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
(82 reference statements)
0
1
1
Order By: Relevance
“…This positive association between G. apicola and experimental N. ceranae infection seems to be very common, as it was found by other authors [56,58,[62][63][64] in trials conducted under very different conditions, addressing infection at different ages, different honey bee subspecies, distinct spore doses, gut regions examined, diets fed, analytical methods, or through the analysis of individual bees or pooled samples. However, others failed to find any association between N. ceranae infection and this bacterium or with any other bacteria [65], while other studies found associations with other bacteria like those of the genera Lactobacillus, Bifidobacterium, Snodgrassella, or Bartonella [61,62,[66][67][68][69], which did not appear to be modified here. Most of these studies used very young bees (24-48 h p.e.)…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…This positive association between G. apicola and experimental N. ceranae infection seems to be very common, as it was found by other authors [56,58,[62][63][64] in trials conducted under very different conditions, addressing infection at different ages, different honey bee subspecies, distinct spore doses, gut regions examined, diets fed, analytical methods, or through the analysis of individual bees or pooled samples. However, others failed to find any association between N. ceranae infection and this bacterium or with any other bacteria [65], while other studies found associations with other bacteria like those of the genera Lactobacillus, Bifidobacterium, Snodgrassella, or Bartonella [61,62,[66][67][68][69], which did not appear to be modified here. Most of these studies used very young bees (24-48 h p.e.)…”
Section: Discussioncontrasting
confidence: 53%
“…were much more susceptible to N. ceranae infection. This may be because newly emerged bees do not have well-developed peritrophic membranes [68] and the absence of this physical barrier may favour the infection of midgut epithelial cells. Although there were no significant differences in the 8-day-old bees studied here, this trend was similar to that on the previous day.…”
Section: Discussionmentioning
confidence: 99%
“…O intestino médio dos insetos é a porta de entrada de nutrientes e compostos químicos Em A. mellifera, o intestino médio é caracterizado por um epitélio simples, com células colunares digestivas com microvilosidades na superfície apical e núcleo esférico, sendo a principal seção do trato digestório com função de secreção de enzimas digestivas e absorção de nutrientes e o lúmen é revestido por camadas acelulares semipermeáveis que formam a matriz peritrófica, sendo mais espessa na região posterior em relação à anterior do intestino médio (Oliveira e al., 2019;Castro et al, 2020;Serra et al, 2021;Carneiro et al, 2022). A matriz peritrófica é composta por fibrilas de quitina, glicosaminoglicanos, glicoproteínas e proteínas, sintetizadas pelas células do intestino médio (Hegedus et al, 2009;Liu et al, 2019) com função de proteger o epitélio contra abrasão mecânica (Hegedus et al, 2009), prevenção de infecções por microorganismos (Lahane, 1997;Kuraishi et al, 2011;Sadlova et al, 2018;Erlandson et al, 2019;Oliveira et al, 2022), toxinas e outras substâncias danosas (Guo et al, 2019), além de promover o aumento da eficiência da digestão (Bolognesi, 2008).…”
Section: Introductionunclassified